2016
DOI: 10.5539/jas.v8n5p107
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Cotton Genotypes for Protein Content, Oil and Fatty Acid Composition

Abstract: The increase in the population at the global level necessitates to explore promising approaches to increase food supply, including protein and oil, to meet the needs of the people. Cotton is one of the most important oil producing crops and cottonseed meal provides important protein nutrients as animal feed. However, information on the genetic basis of cottonseed oil and protein contents is lacking. In this study; protein contents, oil and fatty acid composition of 124 cotton genotypes were observed for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…The response of nutrients in each year was different. Researchers screened 20 cotton genotypes for protein and oil and found that the frequency distribution showed normal distribution, and differences in protein and oil were significantly different among genotypes [64]. In addition, they reported that the relationship between protein and oil was inverse and complex.…”
Section: Discussionmentioning
confidence: 99%
“…The response of nutrients in each year was different. Researchers screened 20 cotton genotypes for protein and oil and found that the frequency distribution showed normal distribution, and differences in protein and oil were significantly different among genotypes [64]. In addition, they reported that the relationship between protein and oil was inverse and complex.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the cotton land area in the US is located in the southern and southeastern regions 2 4 . Although cotton is mainly planted for its fiber, for every 100 kg of lint fiber ginned from cotton, 150 kg of cottonseed is produced 5 – 7 . The cottonseed mainly contains lipids, proteins, carbohydrate, and minerals 8 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Cotton ( Gossypium spp.) is an important plant that provides raw materials to the textile, food and feed industries [ 1 ]. Biotic and abiotic stress factors in cotton cause a decrease in yield and quality.…”
Section: Introductionmentioning
confidence: 99%